2017
DOI: 10.1016/j.neuron.2017.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA Translation in Neurons—A Matter of Life and Death

Abstract: SUMMARY Dynamic regulation of mRNA translation initiation and elongation is essential for the survival and function of neural cells. Global reductions in translation initiation resulting from mutations in the translational machinery or inappropriate activation of the integrated stress response may contribute to pathogenesis in a subset of neurodegenerative disorders. Aberrant proteins generated by non-canonical translation initiation may be a factor in the neuron death observed in the nucleotide repeat expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
167
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 241 publications
3
167
0
Order By: Relevance
“…These deficits in HD can emanate from one or more of the effects of mHtt on functions, such as vesicle-and microtubule-associated protein/organelle transport, transcription, autophagy as well as tissue maintenance, secretory pathways, and cell division (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). mRNA translation is crucial for cell growth and survival, and increasing data indicates that its dysregulations contributes to neurodegenerative disorders (22,23). We previously identified mHtt as a potentiator of amino acid-induced mTORC1 signaling in association with Rheb and found that the selective upregulation of mTORC1 in the striatum worsened HD behavioral defects (24).…”
Section: Introductionmentioning
confidence: 99%
“…These deficits in HD can emanate from one or more of the effects of mHtt on functions, such as vesicle-and microtubule-associated protein/organelle transport, transcription, autophagy as well as tissue maintenance, secretory pathways, and cell division (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). mRNA translation is crucial for cell growth and survival, and increasing data indicates that its dysregulations contributes to neurodegenerative disorders (22,23). We previously identified mHtt as a potentiator of amino acid-induced mTORC1 signaling in association with Rheb and found that the selective upregulation of mTORC1 in the striatum worsened HD behavioral defects (24).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we employed the tRNA-FRET technique to establish a novel method that enables the visualization and quantification of both tRNA dynamics and mRNA translation at a subcellular resolution (8,9). We focused on global mRNA translation, whose delicate balance may distinguish between health and disease (10,11). tRNA-FRET offers specific focus on neuronal sub-compartments and the identification of local translation events with precise temporal and spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, the spatiotemporal localization of mRNA translation is of paramount importance due to their unique morphology. In neuronal processes, which often traverse distances several orders of magnitude larger than the cell body, the regulation of local translation is fundamental for maintaining their distinct functionalities, including signaling and synaptic plasticity (1,11,94,99).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragile X syndrome, the most common inherited form of intellectual disability, results from the loss‐of‐function of a translational regulator, FMRP, and the failure to repress translation of specific mRNAs in neurons (Darnell & Klann, ). Mutations in AARSs other than VARS have been identified in numerous neurological disorders including peripheral neuropathy, epilepsy, intellectual disability, and microcephaly (Coughlin et al., ; Kapur & Ackerman, ; Kapur, Monaghan, & Ackerman, ; Kodera et al., ; Musante et al., ; Nakayama et al., ; Tsai et al., ; Zhang et al., ). Unlike VARS, these other AARSs are not associated with the eEF1B complex, and there is no evidence that the clinical mutations have arisen in neuronal‐specific transcripts.…”
Section: Why Do Mutations In Genes With Housekeeping Functions Lead Tmentioning
confidence: 99%